2020
DOI: 10.3389/fpls.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic Leaf Development of the Aquatic Plant Callitriche palustris L. Through Differential Cell Division and Expansion

Abstract: Heterophylly, or phenotypic plasticity in leaf form, is a remarkable feature of amphibious plants. When the shoots of these plants grow underwater, they often develop surprisingly different leaves from those that emerge in air. Among aquatic plants, it is typical for two or more distinct leaf development processes to be observed in the same individual exposed to different environments. Here, we analyze the developmental processes of heterophylly in the amphibious plant Callitriche palustris L. (Plantaginaceae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
0
21
0
1
Order By: Relevance
“…diminutive stature and ease of laboratory culture make Callitriche an attractive model for eco-evolutionary investigations of diverse aspects of amphibious life in plants, including stomatal suppression induced by submergence. We recently described the dramatic suppression of stomatal development in submerged leaves of C. palustris (23). We also found that both aerial and The diversity of stomatal development regulation in Callitriche is related to the intrageneric diversity in lifestyles submerged leaves of this species differentiate stomata during a restricted developmental period, when the leaf primordia are ∼1 mm long (23).…”
Section: Significancementioning
confidence: 91%
See 4 more Smart Citations
“…diminutive stature and ease of laboratory culture make Callitriche an attractive model for eco-evolutionary investigations of diverse aspects of amphibious life in plants, including stomatal suppression induced by submergence. We recently described the dramatic suppression of stomatal development in submerged leaves of C. palustris (23). We also found that both aerial and The diversity of stomatal development regulation in Callitriche is related to the intrageneric diversity in lifestyles submerged leaves of this species differentiate stomata during a restricted developmental period, when the leaf primordia are ∼1 mm long (23).…”
Section: Significancementioning
confidence: 91%
“…S8 D and E). In C. palustris, cell proliferation occurred in the basal region of the leaf blade (23), as in C. japonica (SI Appendix, Fig. S8C), and SPCH orthologs were expressed in dividing cells in both species.…”
Section: Amphibious Species Lack Amplifying Divisions In the Stomatalmentioning
confidence: 92%
See 3 more Smart Citations